Between possible and impossible: Argentina’s geodetic topographic projects (1912-1950) - Mazzitelli Mastricchio, Malena (Universidad Pedagógica y Tecnológica de Colombia, 2019)
In 1912, the Military Geographic Institute (IGM) proposed a national cartographic plan which entailed a geodetic survey for the measurement of vertical points and of geographic coordinates. The project was deemed an improvement over other existing measurements. However, the IGM plan turned out to be a very ambitious one, and despite having been adjusted on several occasions, it was not until the end of the 1940s that its objectives could be met. This work seeks to put the pieces back together of the practices deployed by the Institute to carry out such plan. To this end, IGM publications at the time the cartographic plan was presented were analyzed. Their analysis allowed to conclude that the projects surpassed not only expectations but also the technical capacity of the country to perform such measurements.